Channels of projectile fragmentation of 16O nucleus in nuclear emulsion. (6th March 2018) - El-Nagdy, M S; Abdelsalam, A; Badawy, B M; Zarubin, P I; Abdalla, A M; Yasin, M Nabil; Saber, A; Mohamed, M M; Ahmed, M M
Abstract: Experimental data are presented on the projectile fragments emitted from non-central collisions of 3.7 A GeV 16 O projectiles with nuclear emulsion. Charges of all projectile fragments are measured carefully and identified using δ -ray distributions. Each distribution is fitted by Gaussian shape and represented one of the possible charges of projectile fragments. Topology of 16 O fragmentation is reported and compared with that obtained at 60 A GeV. The multiplicity distributions for 16 O projectile fragments with charge 3 ≤ Z ≤ 7 are studied and it classified according to the size of the target nucleus. In this range of energy, the mechanism responsible for projectile fragmentation is independent on its energy. Experimental observations proved that there is high probability for production α -clusters than all other nuclear fragments. The production rate of α -clusters fragments due to 16 O fragmentations is studied at range of energies 2–200 A GeV. The dependence of α -clusters on target components (CNO and AgBr) is formulated. Experimental data indicates that α -cluster represents the main unit of the structure of atomic nucleus.